The shock index predicts acute mortality outcomes in stroke. (1st March 2015) - McCall, Stephen J.; Musgrave, Stanley D.; Potter, John F.; Hale, Rachel; Clark, Allan B.; Mamas, Mamas A.; Metcalf, Anthony K.; Day, Diana J.; Warburton, Elizabeth A.; Bachmann, Max O.; Myint, Phyo K.; ,
Abstract: Background: Shock index (SI) (ratio between heart rate and systolic blood pressure) has been shown to be associated with poor mortality outcomes in trauma and pneumonia; however it has yet to be examined in stroke. We aimed to examine the relationship between SI and acute outcomes of inpatient, 3-day and 7-day mortality in stroke. Secondly, we aimed to compare SI and systolic blood pressure (SBP) alone in predicting above outcomes. Methods: Data from a multicentre prospective cohort study conducted between October 2009 and September 2012 in eight NHS trusts in East of England were analysed. The relationships between SI, SBP and study outcomes were assessed using multivariable logistic regression models using mid-quintile groups as the reference category. Receiver operating characteristic (ROC) curves assessed the discriminating ability between the SI and SBP models. Results: A total of 2121 stroke patients were included (47.4% men; mean age 77.10 (sd) 12.40) years. The lowest quintile of the SI, had an increased odds of 3-day and 7-day mortality, adjusted odds ratio (AOR) 2.45 (95% CI:1.16–5.17) and 1.88 (1.01–3.49), respectively. Patients with the highest quintile of SI also had increased odds of in-patient, 3-day and 7-day mortality, AORs 1.85 (1.17–2.92), 2.18 (1.03–4.63) and 2.45 (1.34–4.49), respectively. Similarly, SBP had a U-shape relationship with mortality. All measures had an ROC area under the curve > 0.8 but there was no difference in the discriminating ability between SI and SBP. Conclusions: SI at extremely high and low values appeared to predict stroke mortality and appears to be particularly useful in predicting very early (3-day) mortality. Highlights: Both the shock index and systolic BP are good at predicting acute stroke mortality. SI and SBP are easily available in a clinical setting, and thus useful prognostic markers. Shock index is particularly associated with 3-day morality in stroke.